When opera meets film - Citron, Marcia J. (Cambridge, UK. : Cambridge University Press, 2010)
'Opera can reveal something fundamental about a film, and film can do the same for an opera, argues Marcia J. Citron. Structured by the categories of Style, Subjectivity, and Desire, this volume advances our understanding of the aesthetics of the opera/film encounter. Case studies of a diverse array of important repertoire including mainstream film, opera-film, and postmodernist pastiche are presented. Citron uses Werner Wolf's theory of intermediality to probe the roles of opera and film when they combine. The book also refines and expands film-music functions, and details the impact of an opera's musical style on the meaning of a film. Drawing on cinematic traditions of Hollywood, France, and Britain, the study explores Coppola's Godfather trilogy, Jewison's Moonstruck, Nichols's Closer, Chabrol's La Ceremonie, Schlesinger's Sunday, Bloody Sunday, Boyd's Aria, and Ponnelle's opera-films'--
Includes bibliographical references, filmography, webliography, and index.
Keywords: Motion pictures and opera; Opera in motion pictures; Musical films -- History and criticism